The literature book (Big ideas simply explained, 2016)
From Fitzgerald's The Great Gatsby to Shelley's Frankenstein, The Literature Book is the ultimate collection of the greatest literature ever written. Documenting over 100 best-selling books, plays and poetry from all over the world, including Latin American and African fiction, The Literature Book encompasses celebrated masterpieces from the most renowned authors to have ever lived. Stunning images and inspirational quotes jump out from the pages, as detailed plot summaries and helpful context bring the timeless works of literature to life. The book also offers a deeper look into the famed fiction of Shakespeare, Oscar Wilde and more, as in-depth literary criticism and interesting authorial biographies give each work of literature a new meaning. In The Literature Book, the world's most iconic literature and greatest writers come together for a fascinating journey through time that is a must-have for any literature student or fan of fiction.